2004
DOI: 10.1111/j.1550-7408.2004.tb00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Foraminiferal Diversity Revealed by Small‐subunit rDNA Analysis of Antarctic Sediment

Abstract: Studies of benthic Foraminifera typically rely on the morphological identification of dried specimens. This approach can introduce sampling bias against small, delicate, or morphologically ambiguous forms. To overcome this limitation, we extracted total DNA from sediment followed by PCR using group- and species-specific primers. Phylogenetic analyses revealed that approximately ninety percent of the PCR products represented previously undescribed sequence types that group with undersampled members of the allog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 26 publications
4
43
1
1
Order By: Relevance
“…Numerous genetic studies revealed cryptic species within planktonic (e.g., de Vargas et al 1999;Darling and Wade 2008), rotaliid (e.g., Holzmann 2000), and monothalamous foraminifera (e.g., Habura et al 2004;Pawlowski et al 2008). Similarly, high hidden diversity within Antarctic planktonic Neogloboquadrina pachyderma sinistral (Darling et al 2004) as well as among monothalamids was revealed using a single-cell sequencing approach (Pawlowski et al 2002b) and by probing environmental DNA (eDNA) extracted from coastal or deep Southern Ocean sediments (Habura et al 2004;Lejzerowicz et al 2014).…”
Section: Discussion Genetic Diversity Of Antarctic Benthic Foraminiferamentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous genetic studies revealed cryptic species within planktonic (e.g., de Vargas et al 1999;Darling and Wade 2008), rotaliid (e.g., Holzmann 2000), and monothalamous foraminifera (e.g., Habura et al 2004;Pawlowski et al 2008). Similarly, high hidden diversity within Antarctic planktonic Neogloboquadrina pachyderma sinistral (Darling et al 2004) as well as among monothalamids was revealed using a single-cell sequencing approach (Pawlowski et al 2002b) and by probing environmental DNA (eDNA) extracted from coastal or deep Southern Ocean sediments (Habura et al 2004;Lejzerowicz et al 2014).…”
Section: Discussion Genetic Diversity Of Antarctic Benthic Foraminiferamentioning
confidence: 99%
“…Similarly, high hidden diversity within Antarctic planktonic Neogloboquadrina pachyderma sinistral (Darling et al 2004) as well as among monothalamids was revealed using a single-cell sequencing approach (Pawlowski et al 2002b) and by probing environmental DNA (eDNA) extracted from coastal or deep Southern Ocean sediments (Habura et al 2004;Lejzerowicz et al 2014). In this study, we tested genetic similarity of common benthic foraminifera from very distant coastal areas of West Antarctica.…”
Section: Discussion Genetic Diversity Of Antarctic Benthic Foraminiferamentioning
confidence: 99%
See 1 more Smart Citation
“…Representatives are known from marginal marine settings to the deep sea, and in selected freshwater settings and terrestrial soils [3]. Molecular studies [4][5] have shown that the biodiversity of allogromiids is considerably higher than that recognized using traditional collecting methods, and as a result we know little about the adaptations and modes of life of this group.The many mudflats associated with the expansive salt marshes of coastal Georgia host an interesting array of mostly undescribed allogromiids in addition to other foraminiferal taxa. Among the new allogromiids is a small (<200 µm) translucent monothlamous species (Fig.…”
mentioning
confidence: 99%
“…Representatives are known from marginal marine settings to the deep sea, and in selected freshwater settings and terrestrial soils [3]. Molecular studies [4][5] have shown that the biodiversity of allogromiids is considerably higher than that recognized using traditional collecting methods, and as a result we know little about the adaptations and modes of life of this group.…”
mentioning
confidence: 99%